Whole-genome sequencing and phylogenetic analysis of Salmonella isolated from pullets through final raw product in the processing plant of a conventional broiler complex: a longitudinal study - Yagya Adhikari; Matthew A. Bailey; Steven Kitchens; Pankaj Gaonkar; Luis R. Munoz; Stuart B. Price; Dianna V. Bourassa; Laura Huber; Richard J. Buhr; Kenneth S. Macklin (Microbiology Spectrum)
ABSTRACT Salmonella are Gram-negative, rod-shaped, entero-invasive foodborne bacteria and are frequently detected in chicken houses and facilities of poultry broiler complexes. The objective of this study was to determine the prevalence, critical entry points, and movement pattern of Salmonella along different stages of a complex. A total of 1,071 environmental samples were collected from 38 production houses (8 pullet, 10 breeder, and 20 broiler), a hatchery, 6 transport trucks, and a processing plant. Samples were screened with 3M Molecular Detection System and were further processed for the confirmation of results. Whole-genome sequencing and phylogenetic analysis were performed to determine genetic relatedness among bacterial strains. Using multivariable model, the odds ratios and 95% confidence limits were compared for stages, sample types, environments, and seasons (α < 0.05). Altogether 18% of samples and 42% of production houses tested Salmonella positive. Interestingly, the odds of Salmonella detection were more likely (P ≤ 0.001) in facilities like hatchery, transport, and processing plant as compared to production farms such as pullet, breeder, and broiler farms. The predominant serotype identified was S. Kentucky followed by S. Enteritidis, S. Typhimurium, S. Johannesburg, S. Montevideo, S. Mbandaka, S. Newport, S. Senftenberg, S. Inverness, S. Ohio, S. Uganda, and N/A (9:z29:-). Phylogenetic analysis showed strong genetic relationship among bacterial strains isolated from different stages. It also suggests diverse movement patterns of bacterial strains and possibility of multiple critical points for bacterial pathogens entering the complex. From the above results, we can conclude that Salmonella from chicken houses/facilities’ environment can enter the broiler complex and can potentially contaminate the final raw product in the processing plant. A multifaceted comprehensive control strategy focusing on both facilities and production farms might be essential for improved control strategies.IMPORTANCESalmonella continues to be the leading human bacterial foodborne pathogen, a serious food safety concern. The major challenges are to reduce the risk of introduction or spread of such bacteria in flocks, to minimize the persistence of such bacteria within the broiler complex, and to achieve USDA FSIS final product standards at the processing plants. Not well understood are the possible entry points and movement patterns of Salmonella along different stages of an integrated broiler complex. For this study, environmental sampling was considered from parent pullets through the final raw product at the processing plant, and SNP-based analysis of Salmonella isolates was conducted to determine the genetic relatedness and movement patterns. Interestingly, the samples from facilities (hatchery, transport, and processing plant) were more likely to be contaminated with Salmonella as compared to production farms (parent pullets, breeders, and broilers). Similarly, the phylogenetic analysis showed strong genetic relationship among strains isolated from different locations within the same stage and between different stages. The results show complex diversity of Salmonella serotypes along the chain and the possibility of multiple critical points for the entry of pathogen into the broiler complex and contaminate the final raw product at the processing plant. Furthermore, improper cooking or handling of contaminated raw chicken meat and meat products with Salmonella and other zoonotic pathogens can potentially cause foodborne illness in humans.